Effects of imagery rescripting on consolidated memories of an aversive film. (March 2019) - Siegesleitner, Marena; Strohm, Miriam; Wittekind, Charlotte E.; Ehring, Thomas; Kunze, Anna E.
Abstract: Background and objectives: Imagery rescripting (ImRs) is a promising intervention targeting emotional memory. Previous analogue studies have mainly investigated effects of ImRs during memory encoding and consolidation; experimental research on the effects and mechanisms of change in ImRs targeting consolidated memories is largely missing. The present study aimed to investigate effects of ImRs on consolidated memories using a multiple-day trauma film paradigm. Methods: Eighty-eight participants were randomly assigned to either ImRs, imagery rehearsal (IRE), or no intervention control (NIC). In Session 1, participants watched an aversive film. In Session 2 (24 h after Session 1), the analogue trauma memory was reactivated and the intervention took place. Participants reported intrusive memories of the aversive film for one week and then returned to the laboratory for a follow-up (Session 3). Results: Compared to IRE, ImRs was experienced as less distressing and elicited less negative emotions. In addition, ImRs accelerated the decline of intrusive memories when compared to NIC. However, ImRs, IRE, and NIC did not differ with respect to the total number of intrusive memories during the week following the intervention. Limitations: There was a floor effect of intrusive memories, which may have obscured a potential superiority of the active interventions over NIC. Conclusions: Adding to the current literature on ImRs as an intervention for emotional memories, the current study underscores that a multiple-day trauma film paradigm can be used to investigate the short-term efficacy and working mechanisms of ImRs, but also points toward useful modifications to the paradigm. Highlights: Imagery rescripting (ImRs) was less distressing than imagery rehearsal (IRE). ImRs, IRE, and no intervention (NIC) did not differ on the number of intrusions. ImRs accelerated the decline of intrusive memories when compared to NIC. A multiple-day trauma film paradigm can be used to investigate ImRs.